The European Employment Strategy. A New Form of Governance of Labour Markets in the European Union - Gudrun Biffl (Austrian Institute of Economic Research (WIFO), 2007)
The European Employment Strategy (EES) has been put in place in order to ensure the survival of the European Social Model in view of institutional change resulting from the introduction of the European Monetary System. It has become the platform of a method of open coordination of social and employment policy. It represents a new method of governance through soft law, as the traditional governance scheme of binding directives failed to find acceptance among member countries in core areas of national policy development and implementation.
Keywords: 330; European Social Model; Open Method of Coordination; Soft Law; National Reform Programme; Supply side management; EU-Wirtschaftspolitik; Sozialstaat; Internationale Wirtschaftspolitik; Governance-Ansatz; EU-Staaten